THE RELATIONSHIP OF AQUATIC PHYSICAL CHEMICAL FACTORS WITH THE DIVERSITY OF SECUUMS (Holothuroidea) IN THE BEACH OF PIA VILLAGE MALUKU DISTRICT - Souhoka, Rian S; Suriani, Sanita; Wakano, Delly (Universitas Pattimura, 2019)
This study aims to determine the relationship between the physical and chemical factors of the waters (Temperature, Salinity, pH, Dissolved Oxygen) and the diversity of sea cucumbers (holothuroidae) in the coastal waters of Pia Hamlet. The method used is the Belt Transect method. Analysis of diversity data using the Shannon-Winner diversity index formula then to determine the functional relationship between sea cucumber diversity and physical and chemical factors of waters was carried out using simple linear regression and multiple linear regression. The results showed that 1 class, 2 orders, 2 families, 3 genera with 5 species, namely Holothuria atra, Holothuria leucopsilota, Holothuria scabra, Bohadschia argus and Synapta maculate. The diversity index value is low with an average value of 0.7214. The temperature measurement results ranged from 28.04°C-30.16°C. Salinity measurement results ranged from 31.21-32.26 ‰. The results of pH measurements ranged from 6.80-7.41. Dissolved oxygen measurement results ranged from 5.96-6.40 mg/L. The results of simple regression analysis showed that dissolved oxygen had a relationship and had a significant effect on sea cucumber diversity. The results of multiple regression analysis explained that salinity and dissolved oxygen, if tested together, had a strong relationship and had a significant effect on sea cucumber diversity.